Investigation of the positioning accuracy of the Cat’s Eye as a reference position in asphere-measuring interferometry - Scholz Gregor; Evers Daniel; Fortmeier Ines (EPJ Web of Conferences)
Fast and accurate asphere and freeform measurements are in high demand by the optics manufacturing industry. Interferometric methods such as tilted-wave interferometry meet these demands but require accurate surface positioning of the specimen along the optical axis, since such measurements are sensitive to such positioning errors. In this work the Cat’s Eye position will be investigated in terms of accuracy and repeatability as a reference position for surface positioning in tilted-wave interferometry. For this purpose, a two-regime method for specimen alignment using different optimization criteria is investigated and its repeatability is evaluated. Accurate and reproducible positioning into the Cat’s Eye position together with interferometric movement tracking will allow accurate specimen positioning along the optical axis, which will significantly reduce the surface measurement errors associated with such misalignment and improve the overall measurement uncertainty.